Pemikiran Ahmad Muhammad Mustain Nasoha tentang Moderasi Beragama sebagai Upaya Mewujudkan Toleransi Kebangsaan di Indonesia: Ahmad Muhammad Mustain Nasoha’s Thoughts on Religious Moderation as an Effort to Realize National Tolerance in Indonesia - Ahmad Muhammad Mustain Nasoha; Egi Ikhwan Pramuja Hafizh; Nayla Khoirun Nadhira; Nur Azizah Assilmi; Zar’in Zahrotun Nisa (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The rise of intolerance and radicalism in Indonesia calls for a moderate religious approach. Ahmad Mustain Nasoha’s concept of religious moderation offers a pathway to strengthen national tolerance. This study explores his ideas using qualitative analysis of his works and interviews with relevant figures. Findings reveal that Nasoha emphasizes balance, rejection of extremism, and the promotion of humanistic values. He also highlights the role of education and religious institutions in shaping moderate attitudes. In conclusion, religious moderation serves as a strategic tool for fostering social harmony and an inclusive national identity.